Frequency of Diabetic Nephropathy, through Renal Resistive Index, among Type 2 Diabetic patients with Normal Albuminuria. - Arsalan Shahid, Saulat Sarfraz, Aroosa Mustafa, Uzma Nasim Siddiqui, Mubashir Ejaz, Amir Khan, Sudhanshuth Akar, Madiha Naseer (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The diabetes mellitus is an old known disease and closely related to the renal impairment as a cause. The exact duration for any damage to renal functions is not known but early detection of any such happening is a requirement. Many measures explain the renal damage, proteinuria is one among them. Still it appears after some damage is done. Aim: To measure the RRI for renal arteries and find frequency of diabetic nephropathy among type II diabetic patients with normal albuminuria. Methods: It was a cross-sectional study performed at Shaikh Zayed hospital Lahore, in collaboration of Diabetes Clinic and Radiology Department during January 2020 to January 2021. Here 300 diabetic patients of type 2, with normal albumin creatinine ratio were selected. Both genders with age above 18 years with albuminuria below 30 mg/g and no known diabetic nephropathy were included. Pregnant women, patients with GFR <60ml/min/1.73m2 and those having any history of renal stones and known CKD patients were excluded. Results: One hundred and seventy seven (59.0%) were males, only 38(12.7%) were above 60 years age, 37(12.3%) were obese and 180(60.0%) had duration of diabetes ≤5 years. There were 60(20.0%) smokers, 106(35.3%) had hypertension and 5.0% had fatty liver of grade III. On ultrasound 75(25.0%) cases had both kidneys with irregular contour while 44(14.7%) had raised Parenchymal & sinus echoes in both kidneys. On RRI, 23.3% of the cases were diagnosed to have diabetic nephropathy with max(RRI) >0.70. Conclusion: Renal resistive indexcan diagnose diabetic nephropathy at early stage. Keywords: Diabetic nephropathy, Renal resistivity index, Type II diabetes mellitus, Normal albuminuria